Immunogenicity comparison of conjugate vaccines composed of alginate and lipopolysaccharide of Pseudomonas aeruginosa bound to diphtheria toxoid - Najafzadeh, Faezeh (Iran J Microbiol, 2014)
BACKGROUND AND OBJECTIVES: Treatment of Pseudomonas aeruginosa infections is greatly hampered by innate and acquired antibiotic resistance. The goal of this study was to compure the immunogenicity of conjugates of P. aeruginosa depolymerized alginate-diphtheria toxoid (D-ALGDT) and P. aeruginosa detoxified lipopolysaccharidediphtheria toxoid (D-LPSDT) in mouse model. MATERIALS AND METHODS: Alginate and LPS were purified from P. aeruginosa strain PAO1. The resulting depolymerized alginate (D-ALG) and detoxified LPS (D-LPS) were covalently coupled to diphtheria toxoid (DT) as a carrier protein with adipic acid dihydrazide (ADH) as a spacer molecule and carbodiimide as a linker. Sterility, safety and pyrogenicity tests were performed. 30 mice in two groups were immunized intraperitoneally on days 0, 14 and 28 with 10 μg of D-ALGDT and D-LPSDT. Conjugates specific antibody levels were also determined by enzyme-linked immunosorbent assay (ELISA). RESULTS: The conjugates were non-toxic and non-pyrogenic. Conjugates of D-ALGDT and D-LPSDT were shown to be safe and to elicit total IgG, IgM, IgA, IgG1, IgG2a, IgG2b and IgG3 antibodies in mice. ELISA results indicated that antibodies titer of D-ALGDT was more than D-LPSDT. CONCLUSION: Immunization with D-ALGDT showed significant increase in all types of antibodies titers in versus D-LPSDT, suggesting D-ALGDT as a vaccine candidate against P. aeruginosa infections.